Factors Influencing Blood Pressure Variability in Hemodialysis Patients - Irasahwadi Irasahwadi; Rizki Andriani; Afrizal Afrizal; Mahanta Qaribi (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2025)
Background: Blood pressure changes during hemodialysis are a common complication and can profoundly impact patient safety and quality of life. Various factors such as individual characteristics, technical aspects of the dialysis procedure, and psychological conditions are suspected to contribute to these blood pressure variability. Objective: This study aims to analyze the relationship between age, dialysis vintage, interdialytic weight gain (IDWG), blood flow rate (BFR), and stress levels with blood pressure variability in hemodialysis patients. Methods: This study uses a cross-sectional design with a quantitative approach. Fifty hemodialysis patients who met the inclusion criteria were selected as respondents. Data were collected through clinical dialysis observation sheets, pre-post dialysis blood pressure measurements, and stress level questionnaires. Data analysis was performed using the chi-square test. Data analysis was performed using the chi-square test. Results: The results showed that 54% of patients experienced changes in blood pressure after hemodialysis. There was a significant relationship between age (p = 0.008), IDWG (p = 0.003), BFR (p = 0.027), and stress levels (p = 0.002) with changes in blood pressure. Meanwhile, the dialysis vintage did not show a significant relationship (p = 0.569). Conclusion: Variability in blood pressure during hemodialysis are influenced by physiological, technical, and psychological factors. Managing hemodialysis patients requires a holistic and individual approach, including IDWG management, BFR adjustment, and stress management. Further research is recommended with a longitudinal design and a larger sample coverage.